Media pembelajaran interaktif : media audio visual berbasis camtasia studio - Hujjatun Nahdiyah, Wike; Rusno, Rusno; Yudiono, Udik (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2025)
This study aims to create a multimedia learning resource for Social Science with a focus on international trade for grade IX students at YBPK 1 Tirtoyudo Junior High Scholl. The research used the Research and Development (R&D) method,specifically the Borg and Gall developpment model. The developpment process consisted of ten stages, including research, planning, product format development,validation, review, field tests, and final product review. The validation test involved three experts in linguistics, materials, and media. Additionally, field trials were conducted with 5 students from YBPK 1 Tirtoyudo Junior Hight School. The main objective of this study was to produce an effective and efficient multimedia learning resourcethat can enhance understanding of international trade among grade IX students. The types of data obtained are qualitative and quantitative data. The results of this study indicate that the development of audio-visual learning products based on camtasia audio for social studies subjects in class IX SMP YBPK Tirtoyudo 1 which are practical to use. This is envidenced by the results of media expert certification getting 90% points so that it is in the very feasible category. The results of validation from material experts with the acquisition of 80% points so that it is in the feasible category. The results of validation from language experts with 85% points so that it is in the very feasible category. Furthermore, the evaluation results from the field trial obtained a score of 88% so that it is in the very good category. Thus the product that has been developed can be concluded to be suitable for use.